Ventilatory Support for COVID-19 Patients - Harky, Amer; Harahwa, Tinotenda A; Khan, Inayat H (Acta Biomedica Atenei Parmensis, 2020)
Coronavirus Disease (COVID-19), first emerged in Wuhan, China, in December 2019 and has now become a worldwide health emergency. The symptoms of Coronavirus vary from anosmia, fever, and cough to severe complications such as acute respiratory distress syndrome, which often require intubation and subsequent ventilation. Procedures such as these are aerosol-generating, and this adds additional challenges due to the risks posed to staff. In this brief article, we discuss the need for ventilation, risks raised to healthcare staff in this context, and ways to potentially mitigate these risks. We also discuss emerging themes, including phenotypes of COVID-19 and the role of prone positioning.